Comparison of Education in New Zealand and Indonesia in Science Subjects in Primary School - Karno, Budi Puspito; Susanti, L. R. Retno; Hudaidah, Hudaidah; Farhan, Farhan (FONDATIA, 2024)
In New Zealand, science education is also tailored to the local context and Maori culture, which provides an additional dimension to science learning in primary school. On the other hand, Indonesia has a different approach to science education in elementary schools. The purpose of this study is to understand the differences in science education approaches in New Zealand and Indonesia and their implications for student learning outcomes in elementary schools. This study uses a comparative descriptive approach to evaluate the differences in the approach to science education in primary schools between New Zealand and Indonesia. The results of this study show that there are significant differences in the approach of science education in primary schools between New Zealand and Indonesia, which has an impact on students' learning outcomes and scientific understanding. New Zealand implements an inquiry-based learning approach supported by adequate laboratory facilities and a more ideal teacher-student ratio. This allows students to engage directly in experiments and observations, which helps them develop critical thinking skills and a deeper understanding of science. In Indonesia, the science learning approach tends to focus on memorization and theory, with limited laboratory facilities and a large number of students per class, which limits the implementation of practice-based learning. As a result, Indonesian students have lower scientific comprehension scores, as seen in the PISA results. Differences in the quality of educational facilities, teaching methods, and time allocation for science learning in both countries are the main factors that affect student learning outcomes.